Detection SYN flooding attacks using fuzzy logic - Tuncer, Taner; Tatar, Yetkin (Ieee Computer Soc, 2008)
Denial of Service attacks are one of the major type of problems in the computer network security. Because they include many other type of attacks they are one of the most frequently used attack methods.. In general, DoS attacks are used to block access to the computer networks or personal computers. SYN flooding attack is the most widespread of the DoS attacks. In these attacks normal SYN packets can not be distinguished from the SYN attack packets. In this paper, we propose a fuzzy logic based system for detecting SYN flooding attacks. Performance of the proposed system has been compared with Cumulative Sum (CUSUM) algorithm. The simulation results show that the proposed system has better performance for low and high intensity attacks than the CUSUM algorithm.
2nd International Conference on Information Security and Assurance -- APR 24-26, 2008 -- Busan, SOUTH KOREA